Duodenogastral reflux and its influence on manifestation of morphological changes of gastric mucosa - Stepanov Yu.M.; Kovalenko A.N.; Salenko А.V. (Medičnì Perspektivi)
Among the diseases of the gastroduodenal zone chronic gastritis (CG) occupies one of the leading positions. One of the main forms of CG is reflux gastritis (RG) based on long-term location of duodenal content in the gastric antrum, so-called duodenal reflux (DR). It is well known that stable inflammatory response of the gastric mucosa (GM) appears under the influence of bile acid and gastric juice, leading to chronic antral gastritis followed by gradual development of atrophy, metaplasia and dysplasia appearance. Therefore the aim of our work was to investigate the influence of the DR on the course of chronic hepatitis and morphological changes in the gastric mucosa. We observed 70 patients with chronic RG, aged from 22 to 59 years, average age – 43,5±1,2 years. The control group consisted of 25 healthy individuals of both sexes aged from 19 to 39 years. As a result it was found out that pain and dyspeptic syndromes caused problems most of all. While studying the content of bile acids in gastric juice of all patients examined it was higher (1,42±0,05 g/L) in comparison with the control group (0,65±0,04 g/L). Content of bile acids in groups of RG patients with atrophy and without it was analyzed. The role of DR as an independent factor of recomposing changes in GM in chronic RG was proved.